2016
DOI: 10.1016/j.clay.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of an active molecule on the surface of halloysite for controlled release application: Interaction, orientation, consequences

Abstract: The goal of the study was to check the possible use of halloysite nanotubes as a controlled release natural antioxidant device with quercetin as the active component. The mineral was thoroughly characterized by various techniques including the determination of particle and tube morphology, specific surface area, pore size and volume, as well as surface energy. The high surface energy of halloysite predicted strong adsorption of active molecules on its surface and consequently difficult release. FTIR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Very few attempts are made to determine the surface energy of the nanotubes, their pore size and volume although these determine both the amount of active molecules accommodated inside the tubes as well as the kinetics and amount of released material. The detailed characterization of halloysite nanotubes done earlier [40,41] showed that their average length is 203 ± 119 nm, external diameter 50 ± 23 nm and internal diameter 15 ± 6 nm accompanied by a pore volume of 0.039 cm 3 Preferential and very strong adhesion of quercetin within the tubes is demonstrated even better by the correlation between the intensity of the vibration appearing at 1563 cm -1 and the amount of quercetin adsorbed on the surface of the tubes. As the correlation presented in Fig.…”
Section: Characterization Of Active Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few attempts are made to determine the surface energy of the nanotubes, their pore size and volume although these determine both the amount of active molecules accommodated inside the tubes as well as the kinetics and amount of released material. The detailed characterization of halloysite nanotubes done earlier [40,41] showed that their average length is 203 ± 119 nm, external diameter 50 ± 23 nm and internal diameter 15 ± 6 nm accompanied by a pore volume of 0.039 cm 3 Preferential and very strong adhesion of quercetin within the tubes is demonstrated even better by the correlation between the intensity of the vibration appearing at 1563 cm -1 and the amount of quercetin adsorbed on the surface of the tubes. As the correlation presented in Fig.…”
Section: Characterization Of Active Nanotubesmentioning
confidence: 99%
“…The detailed study of the release characteristics of the quercetin/halloysite complex has shown that numerous factors must be considered, which are often partially or completely neglected [40,41]. Very few attempts are made to determine the surface energy of the nanotubes, their pore size and volume although these determine both the amount of active molecules accommodated inside the tubes as well as the kinetics and amount of released material.…”
Section: Characterization Of Active Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ennek fényében tehát olyan HNT/polimer kompozitokat tanulmányoztunk, melyekben különbözõ stabilizátorokat juttatunk be a HNT csövek belsõ felületére (5. ábra), hogy idõben hosszan elnyújtott stabilizáló hatást érjünk el például poliolefinekben. 36,37 A töltõanyag jellemzése során, az irodalomban egyedülálló módon, inverz gázkromatográfiával határoztuk meg az ásvány felületi energiáját, aminek döntõ szerepe van a kölcsönhatások erõsségében. Részletes vizsgálatainkkal bizonyítottuk, hogy az antioxidáns molekulái preferáltan kötõdnek meg a nanocsövek belsõ felületén és az összetétel helyes megválasztása mellett, elnyújtott stabilizáló hatás is biztosítható a módosított nanocsövekkel.…”
Section: Mûanyag-és Gumiipari Laboratóriumunclassified
“…5 Due to various pharmacological and biological applications of quercetin and its metal complexes, adsorption and extraction of quercetin from natural resources have been extensively investigated. Porous organic materials, including silica nanoparticles, 6 polytetrauoroethylene lms, 7 macroporous acrylic resin 8 and halloysite, 9 have been employed in the adsorption and extraction of quercetin. However, most of these materials cannot be effectively recycled.…”
Section: Introductionmentioning
confidence: 99%